editorial board - Srinakharinwirot Research; Development Journal of Humanities; Social Sciences (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
Srinakharinwirot Research and Development Journal of Humanities and Social Sciences